2019
DOI: 10.1016/j.electacta.2018.10.157
|View full text |Cite
|
Sign up to set email alerts
|

Self-supporting carbon nanotube films as flexible neural interfaces

Abstract: Advances in neural interface technologies have sought to identify electroactive materials that are able to translate neural depolarisation events into digital signals or modulate neural firing through ionic or electrical stimulation with greater efficiency. An ideal material for neural recording and/or stimulation should possess low electrical impedance coupled with a high cathodic charge storage capacity (CSC C ), charge injection capacity (CIC) and electroactive surface area (ESA), as well as optimal mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…One strategy is increasing the electrochemical surface area of the electrode to expand its electric double layer (EDL) capacitance, mainly including rough treatment (e.g., roughed Pt [23,24] ) and materials with large specific surface area (e.g., carbon nanotubes, [25,26] graphene, [27] etc. [28][29][30] ). However, most roughing methods are rather complex, for example, laser roughening for Pt.…”
Section: Introductionmentioning
confidence: 99%
“…One strategy is increasing the electrochemical surface area of the electrode to expand its electric double layer (EDL) capacitance, mainly including rough treatment (e.g., roughed Pt [23,24] ) and materials with large specific surface area (e.g., carbon nanotubes, [25,26] graphene, [27] etc. [28][29][30] ). However, most roughing methods are rather complex, for example, laser roughening for Pt.…”
Section: Introductionmentioning
confidence: 99%
“…It was again noted that EDL:Ag 10:1 coated electrodes possess the highest CIC, greater than the CIC observed with both pristine EDL coated and bare Pt electrodes. Furthermore, among all investigated materials EDL:Ag 10:1 provided the most stable and controlled amount of injected charge, and the high CIC allows for the use of low electrical potentials without compromising the therapeutic effects of stimulation [ 45 ]. A comparison of the CIC values with respect to the AgNWs content in EDL:Ag composites indicated that lower AgNWs contents reduced the CIC, a phenomenon previously shown to be due to the lack of a robust percolation network [ 46 ], preventing the effective release of stored charge.…”
Section: Discussionmentioning
confidence: 99%
“…Their density, stiffness, and topography can be controlled [ 72 74 ], and they can be synthesized on, or transferred to, flexible substrates [ 75 , 76 ]. Due to a combination of their chemical composition and surface texture, CNTs promote neuronal adhesion and increase the number of processes and their growth [ 77 79 ]. Choosing from various topographies [ 80 , 81 ], we adopt a vertically-aligned CNT (VACNT) approach in which a conducting ‘forest’ of tangled CNTs is patterned on a smooth silicon dioxide (SiO 2 ) substrate.…”
Section: Introductionmentioning
confidence: 99%